2020
DOI: 10.1101/2020.11.28.402065
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Orbitofrontal-hypothalamic projections are disrupted in hypermetabolic murine ALS model and human patients

Abstract: Increased catabolism is a new clinical manifestation of Amyotrophic Lateral Sclerosis. A dysfunction of lateral hypothalamus may drive hypermetabolism in ALS; however, Its causes and anatomical substrates are unknown. We hypothesize that disruption cortico-hypothalamic circuits may impair energy homeostasis in ALS. We used rAAV2 for large-scale projection mapping and image analysis pipeline based on Wholebrain and Ilastik to quantify projections from the forebrain to the latera hypothalamus of the SOD1(G93A) A… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 69 publications
(88 reference statements)
0
2
0
Order By: Relevance
“…Amyotrophic lateral sclerosis (ALS) is a neuromuscular disorder characterized by progressive muscle atrophy and paralysis, in which the affected individual eventually dies of breathing failure. ALS is characterized by both upper and lower motor neuron dysfunction, but is not limited to these regions, eg, structural or functional impairment in the middle temporal gyrus, 1 insula, 2 , 3 anterior cingulate gyrus 4 and some regions within the occipital and parietal lobes. 5 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Amyotrophic lateral sclerosis (ALS) is a neuromuscular disorder characterized by progressive muscle atrophy and paralysis, in which the affected individual eventually dies of breathing failure. ALS is characterized by both upper and lower motor neuron dysfunction, but is not limited to these regions, eg, structural or functional impairment in the middle temporal gyrus, 1 insula, 2 , 3 anterior cingulate gyrus 4 and some regions within the occipital and parietal lobes. 5 …”
Section: Introductionmentioning
confidence: 99%
“… 6 Neuroimaging studies have observed that hypothalamus atrophy in ALS in the premorbid stage and correlates with body mass index (BMI). 8 Furthermore, a diffusion tensor imaging study demonstrated the selective involvement of orbitofrontal, insular, and motor cortex projections to the hypothalamus in murine ALS models and human patients, 3 and some studies showed that neurons of the hypothalamus innervate various subcortical motor structures such as the cerebellum, vestibular nuclei 9 and even spinal cord, 10 which may be associated with motor dysfunction in ALS.…”
Section: Introductionmentioning
confidence: 99%